Beyond the beat: a narrative case study of identity, belonging, and holistic growth through brass band participation in Malaysian secondary education - Yong, Lai Tee; Ong, Peter (College of Creative Arts, 2025)
Co-curricular participation has long been part of Malaysia’s educational vision, yet its deeper role in shaping identity and belonging remains underexplored. This study investigates how membership in the Jabatan Seni Persembahan Orkestra (JSPO) brass band in Penang fosters discipline, emotional growth, and civic identity among secondary school students. Using a narrative case study design, eight band members aged 14 to 17 were purposively selected and engaged through semistructured interviews, naturalistic observations, and document analysis. Data were thematically analysed using Braun and Clarke’s framework, guided by sociocultural learning theory and Eisner’s concept of the hidden curriculum. Findings indicate that brass band participation cultivated self-discipline, resilience, and emotional regulation while creating a sense of family-like belonging across ethnic and social boundaries. The band also functioned as a symbolic and civic space, where wearing the uniform and performing patriotic repertoire reinforced accountability and national pride. This research contributes to the limited Malaysian scholarship on music and identity by showing how brass bands operate not as supplementary co-curricular activities but as pedagogical ecosystems that align with the Pelan Pembangunan Pendidikan Malaysia (PPPM) 2013–2025 and Malaysia MADANI aspirations. Implications are offered for policymakers, educators, and school leaders seeking to reposition arts education as central to holistic student development.